(untitled) (Bangladesh Medical Journal, 2021)
Along with different carbapenemase encoding genes, in recent year class D OXA enzymes are documented in Proteus spp which are not common in Enterobacteriaceae. The dissemination of plasmids, transposons and integrons among bacteria and species playing roles for this dissemination. So, this study was designed to observe the emergence and distribution of different classes of carbapenemase encoding genes among imipenem resistant Proteus spp. isolated from tertiary care hospital in Bangladesh. Total 15 imipenem resistant Proteus isolates were included in this study, which were collected from wound swab, pus, urine and blood samples. Identification was done by culture and biochemical test and antibiotic susceptibility test was done by disc diffusion method. MIC of imipenem (g/ml) was done among imipenem resistant P. mirabilis by agar dilution method. blaKPC, blaNDM-1, blaVIM, blaIMP, blaOXA-48 like, blaOXA-23 like, blaOXA-51 like, blaOXA-58 like carbapenemase encoding genes were detected among imipenem resistant Proteus spp. by PCR and sequencing of blaOXA-48 like, blaOXA-51 like gene done by capillary method to compare the sequences with the same gene, available in gene bank. Among 15 imipenem resistant isolates blaNDM-1 (26.67%), blaKPC (20%), blaVIM (20%), blaOXA-484 (20%) were predominant carbapenemase encoding genes followed by blaOXA-66(6.67%). This study finds that blaOXA-484 gene and blaOXA-66 class D carbapenemase encoding genes are emerging in Proteus spp. and may play a contributing factor in developing carbapenem resistance. Bangladesh Med J. 2020 May; 49(2) : 1-8